Fast American Option Pricing: The Double‐Boundary Case. Issue 116 (22nd November 2021) - Andersen, Leif; Lake, Mark
Abstract : Leif Andersen and Mark Lake consider how to adjust integral‐based numerical techniques for American options to the special situation where the exercise region has a "double boundary."